Cultural Change Reflected In Arthur Miller s Death Of A Salesman Drama (1949): A Sociological Approach - Permatasari, Mei Intan, Dr. M. Thoyibi, M.S (2017)
This study is about the Cultural Change Reflected in Arthur Miller's Death of a Salesman Drama (1949), which is analyzed by using sociological approach. The objectives of this study are to identify elements of cultural change, to depict how culture change is happened, to reveal why Arthur Miller gives his concerns on the issues of cultural change in the drama Death of a Salesman based on Sociological approach.This study belongs to qualitative research. The primary data from this study is a drama by Arthur Miller titled Death of a Salesman, published in 1949, while the secondary data from this study is another source involved in the study, such as: references online, and some books that support this research. The researcher draws three conclusions in this study. First, the cultural changes that occur in the elements of cultural change as the change of equipment, livelihood systems, kinship and system of organizations, and language. Second, the cultural changes that portrayed in the play through the structure include a plot, characters, events, and style. Thirdly, the reason of the author to give concern about changes in people's views of the American Dream that has deviated from the norms and values inherited from our ancestors.